Increasing Production, Improving Product Quality, and Empowering the Cracker Entrepreneur Group in Ngelom Pesantren Village - Qurrota A'yuni; Alfa Akustia Widati; Yanuardi Raharjo; Pratiwi Pudjiastuti; Tokok Adiarto; Muji Harsini; A. Budi Prasetyo; Ganden Supriyanto; Handoko Darmokoesoemo; Adiba Naila Izzah; Hamizah Haula'; Hamzah Hilmy Hermawan; Almaysh Haidar Rizqullah (Institut Pertanian Bogor, 2026)
This community service aims to assist by disseminating technology related to production equipment, which will help increase both the quantity and quality of products. Additionally, the program offers training on oil quality and teaches how to process waste cooking oil into soap. This community service activity is a way to achieve SDGs in the Decent Work and Economic Growth category through Small Entrepreneur and the Rural Economy. The activities were held in Ngelom Pesantren Village from April until September 2023 to overcome the priority problems that exist in the cracker entrepreneur group. The participants of this activity were a group of cracker entrepreneurs in Ngelom Pesantren Village, totaling 30 participants. Activities were carried out through research methods, workshops, and procurement of tools to improve the production process and quality of cracker products. The workshop topics covered halal certification of food products, oil quality standards, and making soap from waste cooking oil. The survey results showed that participants had a satisfaction level of 92% towards the activities and 93% towards the procurement of tools provided, and the production increased by 202.78%. In addition, the crackers are less greasy and the packaging is well-sealed, which can improve the quality of cracker products.